Results of doppler investigation of blood flow velocity in reduced inflow or increased resistance in the brachial artery - CHROŚCICKI, A.; SECOMSKI, W. (Archives of Acoustics, 2015)
Recordings of the blood velocity in the brachial artery were made in healthy persons by means of Doppler ultrasound, ECG and phonocardiography methods. The blood inflow to the brachial artery was reduced at first by a mechanical occluding of the axillary artery, simulating conditions similar to the aortic stenosis, low cardiac output and obstructive cardiomyopathy. In the second stage, peripheral resistance was increased by compression of the forearm, clenching fist or elevation of the upper extremity. In the last stage, respiration influence of arterial and venous flows was evaluated.